A Prokineticin (PK)-like cytokine from Chinese mitten crab Eriocheir sinensis promotes the production of hemocytes via reactive oxygen species. Issue 77 (June 2018) - Jia, Zhihao; Wang, Mengqiang; Wang, Xiudan; Xu, Jiachao; Wang, Lingling; Zhang, Huan; Song, Linsheng
Abstract: Astakine is a cytokine-like factor containing a prokineticin domain, which directly participates in hematopoiesis and blood cell differentiation. In the present study, a novel Astakine gene was identified from Chinese mitten crab Eriocheir sinensis (designated as Es Ast). The full-length cDNA of Es Ast was of 1163 bp, consisting of a 5′ untranslated region (UTR) of 120 bp, a 3′ UTR of 656 bp, and an open reading frame (ORF) of 387 bp encoding a polypeptide of 128 amino acids. There were a signal peptide and a prokineticin domain with nine conserved cysteine residues in the deduced amino acid sequence of Es Ast. Es Ast shared higher similarity with Astakines from Penaeus monodon and Pacifastacus leniusculus, and it was closely clustered with the Astakine from shrimp P. monodon in the phylogenetic tree. The Es Ast mRNA transcript was higher expressed in hemocytes and hepatopancreas. The relative expression level of Es Ast in hemocytes was continuously increased from 1.5 to 48 h after Vibro anguillarum challenge compared that in the untreated control group. After Pichia pastoris GS115 challenge, the relative expression level of Es Ast in hemocytes was also up-regulated. After r Es Ast injection, ROS levels in HPT cells were also increased at 12 and 24 h, and the total hemocyte counts were also significantly increased at 6, 9, 12, and 24 h post r Es Ast injection. The interference of Es Ast expression with dsRNA injection could delay the recovery of hemocytes production post A. hydrophila stimulation. When mitochondrial complexes I was knock down by dsRNA, ROS levels were decreased and THCs were also decreased. Recovery of hemocyte production inducing by A. hydrophila stimulation and r Es Ast injection were delayed with ds Es bc1 injection. When ROS levels were increased after RNAi of Lon protease, THCs were also increased. The expression levels of five genes ( Es JNK, Es STAT, Es PI3K, Es AKT1, Es P70S6K) involved in SAPK-JNK and mTOR signaling pathways were up-regulated at 12 and 24 h in r Es Ast group and Es Lon dsRNA group compared with that in EGFP dsRNA group, and were similar to the trend of ROS levels. These results collectively suggested that Es Ast should be a novel Astakine to promote the production of hemocytes in a ROS-dependent way in E. sinensis . Highlights: An Astakine was identified in Chinese mitten crab Eriocheir sinensis. r Es Ast treatment could induce production of hemocytes and increase ROS level in HPT. RNAi for ROS production genes could block the hemocyte production induced by Es Ast.